2015
DOI: 10.5897/ajb2014.13958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera Lam. aqueous leaf extracts on follicle stimulating hormone and serum cholesterol in Wistar rats

Abstract: The study e and serum were used. animals we Graded dos the first ph male and E rats, 10%. experiment The results (p<0.05). Th male and fe stimulating decreased observed to male and f lowering th revealed a d Key words: TRODUCTION e therapeutic ian subcontin own as, a rem Corresponding a uthor(s) agree t ternational Lice 181-186, 21 Ja AJB2014.13958 r: C474401497 5 015 n the copyrigh cademicjourn Research s of Mo icle sti Nwamara Department of 2 Departme evaluated the cholesterol. The male ere grouped ses (1, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The secretion of both gonadotropins was markedly increased in group 5 rats, possibly due to the presence of the potent antioxidants: vanillin, tannins, phenolics and especially flavonoids and carotenoids found in M. oleifera leaves, which have the ability to alter androgen levels (Gopalakrishnan, 2016). The increased secretion of gonadotropins is consistent with previous reports of Nwamarah et al (2015) and Manhal et al (2017).…”
Section: Discussionsupporting
confidence: 89%
“…The secretion of both gonadotropins was markedly increased in group 5 rats, possibly due to the presence of the potent antioxidants: vanillin, tannins, phenolics and especially flavonoids and carotenoids found in M. oleifera leaves, which have the ability to alter androgen levels (Gopalakrishnan, 2016). The increased secretion of gonadotropins is consistent with previous reports of Nwamarah et al (2015) and Manhal et al (2017).…”
Section: Discussionsupporting
confidence: 89%
“…The decrease in the laying percentage might be attributed to the negative effect of M. oleifera on the follicle stimulating hormone of laying hens (Ajuogu et al, 2019) which resulted to decreasing the laying potential. There was a reported decrease in FSH of female Wistar rats administered graded levels of M. oleifera leaf extract, where the control produced significantly higher amount of FSH compared to the experimental groups (Nwamarah et al, 2015). Ladokun et al (2015) also reported a significant decrease in the concentration of FSH in WAD bucks fed moringa leaves on the 4 th and 8 th weeks of the experiment.…”
Section: Resultsmentioning
confidence: 94%
“…Tamarind fruit contains tannin, saponin, sesquiterpenes, alkaloids, and phlobatannins (Silalahi, 2020). Moringa leaf extract (Jain et al, 2010;Nwamarah et al, 2015;Saleem and Naureen, 2021), kersen leaf (Alimar et al, 2022), bay leaf bark (Sutrisna et al, 2018), and okra fruit extract (Rahayuningsih et al, 2018) were also reported to decrease blood cholesterol of Wistar rats or exhibiting a hypolipidemic effect. Moringa leaf extract contains phenolics, flavonoids, and condensed tannins.…”
Section: Introductionmentioning
confidence: 99%